2019
DOI: 10.5588/ijtld.18.0324
|View full text |Cite
|
Sign up to set email alerts
|

NAT2 variants and toxicity related to anti-tuberculosis agents: a systematic review and meta-analysis

Abstract: (TB) patients receiving anti-tuberculosis treatment may experience serious adverse drug reactions (ADRs) such as hepatotoxicity. Variants of the N-acetyltransferase 2 (NAT2) gene may increase the risk of experiencing such toxicity events. O B J E C T I V E : To provide a comprehensive evaluation of the evidence base for associations between NAT2 variants and anti-tuberculosis drug-related toxicity. M E T H O D : This was a systematic review and metaanalysis. We searched for studies in Medline, PubMed, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 73 publications
3
24
0
4
Order By: Relevance
“…By considering the difference of NAT2 acetyl phenotype and by combining it with the PBPK/PD model, doctors can adjust the dose of isoniazid to improve its therapeutic effect. Therefore, the detection of new Asian phenotypes by screening NAT2 gene polymorphism in different races is meaningful for clinical prediction and prevention of adverse reactions …”
Section: Discussionmentioning
confidence: 99%
“…By considering the difference of NAT2 acetyl phenotype and by combining it with the PBPK/PD model, doctors can adjust the dose of isoniazid to improve its therapeutic effect. Therefore, the detection of new Asian phenotypes by screening NAT2 gene polymorphism in different races is meaningful for clinical prediction and prevention of adverse reactions …”
Section: Discussionmentioning
confidence: 99%
“…We assume, based on data from meta-analyses, that individuals with rapid metabolizer phenotypes are more likely to fail treatments than slow and intermediate metabolizer phenotypes (risk ratio, 2.02) [ 27 ]. Conversely, we model INH hepatotoxicity to be more common among slow and intermediate metabolizer phenotypes than rapid metabolizer phenotypes (odds ratio, 3.68 and 1.12, respectively) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…NAT2 genotype predicts clinically relevant endpoints as well. Multiple studies have revealed that slow acetylators are at increased risk of drug-induced liver injury from INH [ 9 ]. A meta-analysis found that rapid acetylators are at increased risk of treatment failure, relapse, and acquisition of resistance [ 7 ].…”
mentioning
confidence: 99%
“…A study conducted in Brazil found that the incidence of INH-induced hepatotoxicity differed among rapid (2.9%), intermediate (9.8%), and slow (22%) NAT2 acetylators [29]. Meta-analysis studies report slow acetylators were significantly more likely to experience hepatotoxicity from INH treatment for tuberculosis than rapid acetylators [30,31].…”
Section: Isoniazid (Inh)mentioning
confidence: 99%